2016
DOI: 10.1017/s1041610216001721
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy as a mediator in use of mental health services among older korean adults

Abstract: Efforts to improve mental health literacy through community-based education programs may need to particularly target Korean older adults with the relevant socio-demographic characteristics to enhance their utilization of appropriate mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…The characteristics of older persons in terms of the prevalence and type of mental disorders, especially AD, require special attention and research (Scazufca et al, 2010;Werner, 2005). Even studies assessing general mental health literacy emphasize that efforts to improve mental health literacy may need to particularly target older adults with relevant sociodemographic characteristics (Kim et al, 2017). This and other limitations make it difficult to assess the representativeness of published results.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of older persons in terms of the prevalence and type of mental disorders, especially AD, require special attention and research (Scazufca et al, 2010;Werner, 2005). Even studies assessing general mental health literacy emphasize that efforts to improve mental health literacy may need to particularly target older adults with relevant sociodemographic characteristics (Kim et al, 2017). This and other limitations make it difficult to assess the representativeness of published results.…”
Section: Discussionmentioning
confidence: 99%
“…Y. S. reported that older adults (age 65 years and older) had difficulty recognizing their mental health issues and had limited knowledge of selfhelp strategies. Y. S. Kim, Rhee, et al (2017) reported in their study of older Koreans in Korea that mental HL was a significant mediator between participants utilization of mental health services and their education, general literacy, and health status.…”
Section: Predictors Of DL and Its Relation To Sociodemographicsmentioning
confidence: 98%
“…Detection of fake news might represent a proxy for other proximal and intermediate causal factors and mechanisms that could explain the acceptance of a vaccine. The mediating role of HL has been assessed in several associations like between socio-economic status and health, 22 population characteristics and use of health services 23 or between education and health outcomes. 24 The role of HL in the relation between detection of fake news and vaccine hesitancy has not been explored, yet.…”
Section: Introductionmentioning
confidence: 99%